PHILOSOPHICAL VIEWS, ABSTRACTION AND HUMAN IMAGE IN THE STORIES OF NAZAR ESHANQUL - Erkinova Maftuna Tulkinjonovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article highlights the human image, abstractness, and philosophical views in the stories of Nazar Eshanqul. Mainly the analysis of modern stories of Nazar Eshanqul was considered.